Psychiatrists' attitudes towards and willingness to prescribe cognitive enhancers in academic settings. (2nd January 2021) - Ram, Sanyogita (Sanya); Russell, Bruce R.; Stewart, Kay; Kirkpatrick, Carl; Henning, Marcus; Scahill, Shane; Hussainy, Safeera
Abstract: Cognitive enhancers (CEs) such as methylphenidate, dexamphetamine and modafinil are increasingly used beyond their prescribed indications by healthy individuals without medical necessity, in academic settings. Prescribing of these stimulant medicines have increased over the last decade. Aim: To explore psychiatrists' attitudes towards the use of CEs in academic settings, and their willingness to prescribe CEs. Methods: The study was conducted via an anonymous, paper-based questionnaire sent to a random sample of 200 psychiatrists in New Zealand. The questionnaire assessed demographics and knowledge of CEs, attitudes towards the use of CEs in healthy individuals, perceptions on the extent of use by university students and attitudes towards, and willingness to prescribe CEs. Results: Of the 200 questionnaires distributed, 81 completed questionnaires were returned, giving a response rate of 40.5% (81/200). Although 19.8% of participants reported receiving requests from university students for CEs, only 6.1% reported prescribing medicines for university students that they considered were for cognitive enhancement. None of the participants would routinely prescribe methylphenidate to a healthy university student. Reasons for not prescribing CEs included concern for safety, being unethical, and not warranted in the absence of illness. Conclusion: Psychiatrists are aware of the use of CEs by students and play a crucial role in prescribing or curbing its use. There was a lack of consensus within the profession on attitudes towards efficacy, the safety of CEs when prescribed and potential for adverse outcomes.